L’émergence d’un nouveau modèle de traduction – théorie et pratique de la traduction multimodale sur l’exemple de la traduction en français de l’album Kłopot d’Iwona Chmielewska - Kochanowska, Anna (Studia Romanica Posnaniensia, 2024)
Translation activity is traditionally perceived as monomodal, focused on the written or spoken word. However, the evolution of contemporary societies, increasingly visual, often pushes the translator to work on a multimodal product, where language is only one of the modes of communication, hence the emergence of models of multimodal translation. The present contribution studies the literary multimodal translation model based on the album Kłopot by Iwona Chmielewska, world-renowned author and illustrator. The contribution hopes to demonstrate the challenges and opportunities of the multimodal translation workshop, seen as a growing professional activity in today’s multimodal societies.